Testing Strategies for Smart Cities applications: A Systematic Mapping Study - Costa, Alex; Teixeira, Leopoldo (Anais do Simpósio Brasileiro de Testes de Software Sistemático e Automatizado (SAST); 2018: Anais do III Simpósio Brasileiro de Testes de Software Sistemático e Automatizado, 2018)
Context: Smart Cities are urban areas that enable the development of applications to improve city resources management, through the use of information technology such as Internet of Things and cloud computing, as well as government data availability and citizen participation. Some challenges identified in the development of solutions for this context are: scalability, modularity and security. Goal: Testing activities are critical to the verification and validation of Smart City solutions, so our goal is to develop a map of test strategies for applications developed in the context of Smart Cities. Method: For this study we defined a systematic literature review protocol to identify, select, analyze and synthesize the results of previously published empirical studies in the software engineering literature, related to testing Smart Cities applications. Results: In this systematic mapping, 13 articles were selected, that have identified test strategies used by developers for the application testing process. We have also identified some difficulties faced in the process of testing these applications through reports present in the works selected in this mapping. Conclusion: Our research synthesized evidence that we hope might serve as a data source for academic research and industrial practice. As future work we plan to apply our results highlighting a case study in real applications to validate the collected evidence.